Sistema para aproveitamento de energia vibracional baseados em transdutores acústicos piezelétricos de baixo custo - Cardoso, Adilson Jair (2006)
This dissertation presents the development of a system for converting the mechanical energy from vibrations into electrical energy. The conversion is performed in a low-cost piezoelectric transducer, commonly known as buzzer. The main purpose of this system is to charge, or to extend the time between charges, of chargeable batteries up to 2V. In order to control the charging process, an integrated energy processor was also designed. Processor design is presented from its specification, followed by circuit topology definition, electric simulation, layout, extraction of circuit from layout and a final simulation including layout effects. The main contribution of the investigation is to show how much energy could be obtained from vibrations with a low-cost transducer, comparing its performance to full custom generators. The final system implementation is very simple, composed by a generator (a buzzer with a steel ball glued onto its center) and an integrated circuit that controls the charge delivered to the battery, sensing the voltage across its terminals. An efficiency of 55% is expected, being comparable to results published by other researchers.